.66(9x-15)=2(3x-5)

Simple and best practice solution for .66(9x-15)=2(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for .66(9x-15)=2(3x-5) equation:



.66(9x-15)=2(3x-5)
We move all terms to the left:
.66(9x-15)-(2(3x-5))=0
We multiply parentheses
5.94x-(2(3x-5))-9.9=0
We calculate terms in parentheses: -(2(3x-5)), so:
2(3x-5)
We multiply parentheses
6x-10
Back to the equation:
-(6x-10)
We get rid of parentheses
5.94x-6x+10-9.9=0
We add all the numbers together, and all the variables
-0.06x+0.1=0
We move all terms containing x to the left, all other terms to the right
-0.06x=-0.1
x=-0.1/-0.06
x=1+0.04/0.06

See similar equations:

| 6x+3/2=1/3 | | 6−6x−3x=0 | | 3n-1n=4 | | 6x-12=61-3x | | 30x+30=-5x | | 7c+3c=50 | | 3+9r^2=12 | | k+18=21 | | 87=10x+-7 | | 2/1x-18=2 | | 3c=-9−6c | | 1/2=-1/4x3/8 | | 6x+10x+35=9x+5 | | 4-3x+6=2(x-25) | | (1/4)x^2=15 | | 1/2=1/4x3/8 | | 6j−2j=8 | | -5j=7−6j | | 3x^2+16x=21 | | 6x=7=3x+16 | | y=-83.7(723.7)-578.9= | | -9b=-10b+3 | | -18=36x+6 | | -11=j/9-13 | | 7.2^x=28 | | v/3+3=6 | | 4=8v-4(v+8) | | y=14.6(-5) | | v3+ 3=6 | | -7=-1+3d | | 2=5+-q | | 3y+3.333=3y-0.5 |

Equations solver categories